Measurement of the differential dijet production cross section in proton-proton collisions at √s= 7 TeV - Işıldak, Bora. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
A measurement of the double-di erential inclusive dijet production cross section in proton-proton collisions at √s = 7 TeV is presented as a function of the dijet invariant mass and jet rapidity. The data correspond to an integrated luminosity of 36 pb-1, recorded with the CMS detector at the LHC in 2010. The measurement covers the dijet mass range 0.2 TeV to 3.5 TeV and jet rapidities up to jyj = 2:5. It is found to be in good agreement with next-to-leading-order QCD predictions.
Keywords: Large Hadron Collider (France and Switzerland); Supersymmetry.